Záchvevy - Wlachovský, Karol; Meisner, Jan (Tatran Bratislava, 1972)
Výber básnického diela slovenských autorov: E.B.Lukáč, J.Smrek, J.Poničan, L.Novomeský, V.Beniak a M.Haľamová.....
Keywords: Poézia; Čítanie študujúcej mládeže; Povinná lit